Internal Bleeding Management in Patient with Blunt Abdominal Trauma at Rural Hospital: A Case Report of 40-Year-Old Male with Spleen Rupture - Harjanti, Erlyn Tusara Putri; Nindra, Bobby; Nindra, Andre (Open Access Macedonian Journal of Medical Sciences, 2023)
Background Abdominal injury caused by blunt trauma is a common presentation in the emergency room.[1] Especially in developing countries like Indonesia, the number of motor vehicle accident in public roads is still high. Eighty percent of traumatic injury is blunt injury with the majority of deaths are caused by hypovolemic shock.[2] Case description A 43-years-old man arrived at the emergency room after motorcycle accident 2 hours before. AMPLE and primary survey was conducted: clear airway, spontaneous breathing, BP 70/palpation mmHg, HR 123 times per minutes and altered consciousness in which showed the patient was undergoing hemorrhagic shock. The patient was hemodynamically stable after given 1 liter of normal saline through two intravenous line. FAST was conducted, intraperitoneal free fluid was seen in Morison’s pouch, left hemithorax, and the pouch of Douglass. Chest X-Ray showed fracture of ribs 7, 8, 9 left lateral aspect with minimal hemothorax. After supporting examination was performed, the patient’s BP dropped to 60/40 mmHg, showed patient was a “transient responder”, indicating the patient should undergo laparotomy. The patient was given 500mL colloid with systolic target 80 – 90 mmHg in accordance to permissive hypotension theory. ±1500ml blood was found inside the abdomen during operation, a splenic rupture grade V was the cause. In the fifth day after surgery, the patient discharged. Conclusion Since blunt abdominal trauma could cause intraperitoneal bleeding that leads to hemorrhagic shock, therefore immediate diagnosis is needed.[1] Multiple trauma management at rural hospital should be concordant to ATLS and Schwartz’s Principles of Surgery.